2018
DOI: 10.1136/jnnp-2017-317515
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment of children born to mothers with epilepsy

Abstract: In utero exposure to AEDs in combination, or sodium valproate alone, is associated with a significant decrease in attainment in national educational tests for 7-year-old children compared with both a matched control group and the all-Wales national average. These results give further support to the cognitive and developmental effects of in utero exposure to sodium valproate as well as multiple AEDs, which should be balanced against the need for effective seizure control for women during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Lacey and colleagues take the innovative approach of using linkage of routine-collected health and national education data to carry out a matched case–control study to assess educational attainment of children born to mothers with epilepsy1. Their main finding was in utero exposure to antiepileptic drugs (AED) in combination, or sodium valproate alone, is associated with a significant decrease in attainment in national educational tests for 7-year-old children compared with both the matched control group and the all-Wales national average.…”
Section: Health Informatics Can Help With the Answermentioning
confidence: 99%
“…Lacey and colleagues take the innovative approach of using linkage of routine-collected health and national education data to carry out a matched case–control study to assess educational attainment of children born to mothers with epilepsy1. Their main finding was in utero exposure to antiepileptic drugs (AED) in combination, or sodium valproate alone, is associated with a significant decrease in attainment in national educational tests for 7-year-old children compared with both the matched control group and the all-Wales national average.…”
Section: Health Informatics Can Help With the Answermentioning
confidence: 99%
“…Recently a Danish study found that children exposed to valproate intuero perform worse then their peers in national tests [33]. Chapter 4 in this thesis presents a study using Welsh Key Stage 1 education tests and AED prescribing data in pregnant women that found inutero exposure to sodium valproate and AEDs in combination are associated with decreased educational attainment in children aged 7 [3].…”
Section: Anti-epileptic Drugsmentioning
confidence: 99%
“…Three different algorithms were tested to identify people with epilepsy within the SAIL Databank. Using a READ codes within GP records, diagnosis codes for epilepsy as well as AEDS were used in the following way For a full list of READ codes used to define epilepsy please see the code list in 3 Data sourced by Beata Fonferko-Shadrach the appendix item 1. 145 of the 150 reference cases with epilepsy (97%) and 143 of the 150 reference cases without epilepsy (95%) were registered with a SAIL GP.…”
Section: Algorithm Validationmentioning
confidence: 99%
See 2 more Smart Citations